The impact of social isolation on cardiovascular disease in the elderly: a systematic review - Marsim, Etanaulia; Salsabil, Husna Arwa; Dwiyovita, Rizka (JHeS (Journal of Health Studies), 2025)
Social isolation can increase mortality and most likely have an impact on health. The impact of social isolation and loneliness on health and well-being is recognised globally as a public health problem. Social isolation can be experienced at any age, especially in the elderly. The purpose of this study was to determine the effect of social isolation on the occurrence of cardiovascular disease in the elderly. This study is a systematic review. Article searches are conducted through databases: PubMed, Science Direct, and Google Scholar with the keywords used in article searches are as follows "Social isolation" AND "cardiovascular disease" AND "elderly". Article selection is done using a PRISMA flow chart. Results: From the results of searching articles in databases obtained as many as 1460 articles that have a relationship with the research theme. Then the article's results were adjusted to the study system used and obtained 565 results that were included in the study system criteria. Then from the 565 articles were re-selected by considering the predetermined inclusion criteria and obtained the results of 10 articles. Conclusion: Social isolation has been shown to be associated with increased risk of cardiovascular disease in older adults. Despite limitations in study design and measurement, these findings underscore the importance of addressing social factors in maintaining the health of older adults.